Effects of exercise training on prostate cancer: Current evidence and potential molecular mechanisms - Madison Webber; Muqing Li; Changmeng Cai; Kai Zou (Advanced Exercise and Health Science)
Prostate cancer (PCa) is a significant health concern globally, being the most diagnosed cancer and the second leading cause of male mortality in the United States. Despite advances in treatment, exploring non-treatment approaches to improve the health outcomes of patients with PCa is crucial. Exercise has emerged as a promising strategy, with evidence suggesting its efficacy in reducing cancer severity, inhibiting tumor progression and metastasis, and promoting less aggressive cancer phenotypes. Observational studies have highlighted a positive association between increased physical activity levels and reduced PCa-specific mortality and disease progression. However, the molecular mechanisms underlying exercise-induced benefits against PCa tumor growth and progression remain poorly understood. Therefore, the purpose of this review is to summarize the pre-clinical and clinical evidence of exercise-induced beneficial effects on PCa tumor growth and outline potential molecular mechanisms by which exercise training attenuates tumor growth and progression. By elucidating the therapeutic potential and molecular mechanisms of exercise training in managing PCa tumor growth, this review aims to inspire further research in this field and offer insights for developing novel therapies that target the molecular alterations with exercise training to treat PCa. It is worth noting that due to the lack of human clinical studies investigating molecular mechanisms responsible for PCa tumor growth, the majority of the data reviewed here is from preclinical models.